The planning-programming-budgeting approach to Government decision-making - Hovey, Harold A. (New York, Praeger, 1968)
This book stands as a major contribution to the growing field of PPB analysis. It describes the PPB approach in terms most readers will find relatively easy to understands, and uses valuable examples from current government activities.
Includes bibliographical references.
rpm 24/01/2018
Loans
Keywords: Expenditure, public; Program budgeting